Experimental Evaluation of Selected Methods for Multigroup Train Formation - Marton, Peter (Communications - Scientific letters of the University of Zilina, 2005)
The purpose of this research project was to compare advantages and disadvantages of selected methods for multigroup train formation. Three simulation models of the marshalling yards were developed to generate and evaluate results for the selected methods. This paper summarizes the steps of the analysis and the results.